AKUNTABILITAS KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR ISLAM TERPADU (SDIT) NURUL ILMI KOTA JAMBI - Sri Marmoah (Universitas Batanghari Jambi, 2013)
The background study of this research is to develop accountability of the headmaster in increasing the quality of education in Islamic center. In this research study, the researcher tries to see and analyze the prevailing condition headmaster in the field of education. The education development especially in managing the management professionalism is quick, as quick as society’s growth. Educational standard appears suit with the needed and society’s ask, and the era development. The problem in this research are formulated as follow: 1). How is the accountability of the headmaster in increasing the quality of education in Islamic center of Nurul Ilmi Jambi, 2). What is the constraint in increasing the quality of education in islamic center of Nurul Ilmi Jambi, 3). What are the efforts that the headmaster do in increasing the quality of education in Islamic center of Nurul Ilmi Jambi. The goals of this research are increasing the quality of education in Islamic center through accountability of the headmaster. The design of the research is using qualitative method. The result analysis can be concluded as follows: First, the accountability of headmaster is make some planning in increasing educational quality for example in academic that is make sure about the curriculum between religion curriculum and general curriculum, based on standard curriculum that has made by government, the school is responsible to develop the curriculum both the material standard (content) and the process of delivering; Second, based on the results of research can be concluded that the barriers of headmaster are the leadership that driving by institute so it’s difficult to the school to make some changes especially in elementary school. It is under the institute that the highest position the Chief all Fondation; Third, the effort of headmaster is joining with the institute. Based on the pool result, the recommendation are: The national education ministry Jambi province to increase the socialization principal of accountability to inproving the quality of education; the headmaster was hoped to do the responsibility as the professional of headmaster, give the best and to do the accountability as the leader, and the school of management, espscially the leader of foundation to more attention of quality, and to do the evaluation to increase of quality.Key Words: Accountability, Headmaster, Quality, Islamic Center.